Creation and development of an Injury Observatory for Britain and Ireland (IOBI). (7th October 2012) - Turner, SL; Lyons, RA; Stone, D; Macey, SM; Barron, S; Slater, W; Brown, P; Verne, J; Lumsden, E; McErlean, I; Quigg, Z; Hughes, K; et al.
Abstract : Background: Many organisations and individuals have a role in injury prevention. However, the majority of these organisations have a multitude of roles, and staff dealing with injury prevention are frequently geographically or professionally isolated. Aims/Objectives/Purpose: The Injury Observatory for Britain and Ireland (IOBI) is an innovative collaboration between the Association of Public Health Observatories and several academic institutions across the UK and Ireland. IOBI supports injury practitioners by providing an accessible injury prevention evidence base. Methods: IOBI emerged from a series of informal meetings of interested professionals in 2004–2005. Being a virtual organisation, IOBI has neither a base nor core funding, though many of the constituent organisations receive funding from central or devolved government agencies. The IOBI website http://www.injuryobservatory.net, established in 2007, supports practitioners by providing access to a range of injury related materials. IOBI launched a free e-newsletter in 2008, Injury Prevention News (IPN, http://www.injuryobservatory.net/_newsletters.html), which is published tri-annually. Results/Outcomes: IOBI members convene two or three times a year to share knowledge, discuss good practice, and to collaborate on injury projects. Key outcomes include: development of a specification enabling comparative analysis of inpatient data across the five countries, a comparative analysis of injury related mortality in the UK and Ireland, organising two national conferences, development of IPN. Significance/Contribution to the Field: IOBI demonstrates the need for a forum for injury prevention collaboration in the British Isles. Its success will ultimately be judged by the extent to which it stimulates an increase in injury prevention practice and research.